Introduction to solid state physics - Kittel, Charles (New Delhi: Wiley India, 2005)
Since the publication of the first edition over 50 years ago, Introduction to Solid State Physics has been the standard solid state physics text for physics majors. The author$1 (Bs goal from the beginning has been to write a book that is accessible to undergraduate and consistently teachable. The emphasis in the book has always been on physics rather than formal mathematics. With each new edition, the author has attempted to add important new developments in the field without sacrificing the book$1 (Bs accessibility and teachability.s
Appendix A-J 641-674p.; Index 675-680p.
Keywords: Condensed matter physics; Physics; Solid state physics; General Science